STUDY ON SWEETENER SELECTION IN RTD TEA BEVERAGES - Hendry Noer Fadlillah; Hari Sakti Ramadhan; Joko Hermanianto; Lira Felanesa (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Tea beverages are getting more popular in Indonesian market. Today, consumers can find tea beverage products in many variants, including ready to drink (RTD) tea beverages. One of the most important ingredient in tea beverages is sugar that provides sweet taste. Due to the increasing concerns on the risk of diabetes mellitus type 2, the Indonesian government has campaigned to reduce sugar consumption. This research purposes were to understand and analyze the type of sweeteners in RTD tea beverages and the producer strategy in reducing sugar. The study was conducted by collecting available RTD tea beverages in modern retail shops. All ingredients on the label was recorded then the correlation with other information on the label and regulation was analyzed. The results showed that all of the sweetened RTD tea beverages (n=58) use sucrose as the sweetener. Sucrose was used singly (81%) or in combination (17%) with other sweeteners. Most RTD tea beverages (60%) used sucralose in combination with sucrose. Others used steviol glycoside (20%) and fructose (20%). There were 24% of the RTD tea beverages that provides claim, 64% of the claim was regarding sugar and calorie. Based on the correlation analysis, it was concluded the tea beverage producers use three strategy in reducing calorie and sugar content in their products, i.e. by 1) totally removing the sugar content, 2) reducing the sweetness level, or 3) combining sucrose with high intense sweetener.